2002
DOI: 10.1055/s-2002-33467
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glucose Transport and Transporter 4 (GLUT-4) in Muscle and Adipocytes of Sucrose-Fed Rats: Effects of N-3 Poly- and Monounsaturated Fatty Acids

Abstract: The goal of this study was to compare the short-term effects of dietary n-3 polyunsaturated (fish oil) and monounsaturated (olive oil) fatty acids on glucose transport, plasma glucose and lipid controls in a dietary insulin resistance model using sucrose-fed rats. The underlying cellular and molecular mechanisms were also determined in the muscle and adipose tissue. Male Sprague-Dawley rats (5 weeks old) were randomized for diets containing 57.5 % (w/w) sucrose and 14 % lipids as either fish oil (SF), olive oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 36 publications
2
34
0
2
Order By: Relevance
“…It is reported that n-3 PUFA causes an increase in insulin sensitivity and/or enzyme activities of carbohydrate metabolism, such as hexokinase, lactate dehydrogenase and glucose-6-phosphate dehydrogenase [24,25] . There is a report on muscle glucose transporter-4 content of rats fed fi sh oil which is similar to that of control rats [26,27] . The decrease in plasma glucose concentrations of mice fed fi sh oil and DHA+EPA or either of these components alone always occurred subsequent to similar changes in total cholesterol and phospholipid concentrations.…”
Section: Discussionmentioning
confidence: 54%
“…It is reported that n-3 PUFA causes an increase in insulin sensitivity and/or enzyme activities of carbohydrate metabolism, such as hexokinase, lactate dehydrogenase and glucose-6-phosphate dehydrogenase [24,25] . There is a report on muscle glucose transporter-4 content of rats fed fi sh oil which is similar to that of control rats [26,27] . The decrease in plasma glucose concentrations of mice fed fi sh oil and DHA+EPA or either of these components alone always occurred subsequent to similar changes in total cholesterol and phospholipid concentrations.…”
Section: Discussionmentioning
confidence: 54%
“…Fish oil also prevents sucrose-induced insulin resistance in rats [41][42][43]. However, the results are controversial as to the capacity of fish oil to reverse insulin resistance once installed after a high sucrose diet.…”
Section: Animal Models Of Insulin Resistancementioning
confidence: 99%
“…Fish oils have a variety of potential cardioprotective effects, including reduction of plasma triacylglycerol concentrations, regulation of blood pressure, amelioration of cardiac arrythmia and reduction in incidence of sudden cardiac death [1][2][3][4][5][6][7]. LC n-3 PUFA supplementation improved insulin sensitivity in normal and insulinresistant rodents [8][9][10][11]. High concentrations of LC n-3 PUFA in plasma and muscle membranes are inversely associated with insulin resistance and protect against the metabolic syndrome in obese human subjects [12,13].…”
Section: Introductionmentioning
confidence: 99%